GAMBARAN DERAJAT DEPRESI PADA PENDERITA KUSTA USIA PRODUKTIF (18-64 TAHUN) - Intan Maharani Sulistyawati Batubara; Nur Setiawati Dewi (Universitas Kusuma Husada Surakarta, 2021)
Leprosy has been a world health problem, a particularly psychosocial burden in the productive age group of people with disability (18-64 years), who are at risk of experiencing a degree of depression. The degree of depression in Leprosy patients is an essential concern for nurses and other health professionals to succeed the health care services, as a matter of consideration to prevent further severe transmission. The purpose of this study was to determine the description of the depression degree in Leprosy productive age patients (18-64 years) in one of a regional public hospital in Jawa Tengah. The type of research was a non-experimental descriptive quantitative research design with a survey approach. This research was conducted on 60 respondents of Leprosy clinic outpatients and inpatients. This research used the WHO Zung Self-Rating Depression Scale questionnaire for a degree of depression. The data were presented in narration and percentages. The study showed that 40 respondents did not experience depression (66,7%), 15 respondents had mild depression (25,0%), four respondents had moderate (6,7%), and one respondent had severe depression (1,7%). Based on these results, depression is a predisposed problem experienced by productive-age-patients who need nurses’ role to identify the degree of depression early so that the other effect of depression can be prevented.